P737 SPOSIB SB2: A Sicilian prospective observational study of patients with inflammatory bowel disease treated with infliximab Biosimilar SB2 (Flixabi®): interim analysis. (25th January 2019) - Macaluso, F S; Cappello, M; Giuffrida, E; Fries, W; Centritto, A; Privitera, A C; Inserra, G; Vassallo, R; Magnano, A; Vinci, E; Garufi, S; Ventimiglia, M; et al.
Abstract: Background: No data on the recently introduced Infliximab (IFX) biosimilar SB2 (Flixabi®) in inflammatory bowel diseases are available. Methods: SPOSIB SB2 is a multi-centre, observational, prospective study performed among the cohort of the Sicilian Network for Inflammatory Bowel Disease (SN-IBD). All consecutive patients with Crohn's disease (CD) or ulcerative colitis (UC) starting IFX Biosimilar SB2 (Flixabi) from the introduction of the drug in Sicily (March 2018) to September 2019 (18 months of enrolment) were or will be eligible. The primary end-point is the assessment of safety, in terms of rate of serious adverse events. Secondary end-points include the evaluation of efficacy, in terms of proportion of patients achieving steroid-free clinical remission and partial response at 8 weeks and at the end of follow-up. Herein we report preliminary data of the first 6 months of the study (March 2018–September 2018). Results: 77 patients (median age 39 years; CD 50.6%, UC 49.4%) were included. Forty-six patients (59.7%) were naïve to anti-TNFs. Sixty-six patients (85.7%) were not previously exposed to IFX, while 8 patients (10.4%) switched form IFX originator to SB2, and 3 (3.9%) from IFX biosimilar CT-P13 to SB2. The cumulative number of infusions of SB2 was 215, the mean follow-up was 2.2 ± 1.7 months (median 1.8 months, interquartile range: 0.4–3.8 months), and the total follow-up time was 14.2 patient-years (170.8 patient-months). Serious adverse events occurred in 7 out of 77 patients (9.1%), with an incidence rate of 49.3 per 100 person-years, and six of them caused the withdrawal of the drug. In details, three infusion reactions, three arthritic flares/arthralgias, and one case of flu-like syndrome were reported. The efficacy of IFX biosimilar SB2 was evaluated in 35 patients who completed at least 8 weeks of follow-up using time-to-event methods for censored observations: 17 patients (48.6%) had steroid-free remission after 8 weeks, 8 patients (22.8%) achieved a partial response, while 10 patients had no response (28.6%). Among the 25 patients with steroid-free remission or response at Week 8, the efficacy rates were 96.6%, 89.1%, and 72.8% after 12, 16, and 20 weeks of therapy, respectively. Conclusions: These are the first data worldwide on the use of IFX biosimilar SB2 in IBD. Our preliminary results showed that efficacy and safety of SB2 seem to be overall similar to those reported for IFX originator and IFX biosimilar CT-P13. Anyway, these data need to be confirmed at the end of the study, when more patients and a longer follow-up will be available.